Konsep Pendidikan Karakter dalam Kitab Tarbiyatul Aulad Fil Islam - Irham, Mohammad Irhaz; Muh Arif; Damhuri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Character education plays a fundamental role in shaping a superior generation in the global era. In Indonesia, systematic efforts to strengthen the character dimension of students are realized through the Merdeka Curriculum. This study analyzes the concept of character education in the book Tarbiyatul Aulad fil Islam by Abdullah Nashih Ulwan and its relevance to the implementation of the Merdeka Curriculum. The research uses a literature review method, focusing on Ulwan's main text and comparative analysis with modern literature. The findings reveal seven pillars of Ulwan's character education—faith, morality, physical, intellectual, psychological, social, and sexual—forming a holistic framework. These pillars align with the dimensions of the Pancasila Student Profile in the Merdeka Curriculum. Implementation challenges include limited teacher understanding, resistance in pluralistic school environments, and limited time allocation. Solutions include integrative training for educators, the formulation of universal values, and the optimization of school culture. The study concludes that Ulwan's concept provides a systematic foundation for the development of a strong-charactered generation, relevant to contemporary educational needs.